Micro-computed tomography assesment of structural microporosity and marginal gaps in different flowable composites placed with different instruments - Burhanettin Avcı; Ebru Nur Uçar; Sezer Demirbuğa; Hacer Balkaya (Cumhuriyet University, 2022)
Objectives: The aim of this study was to evaluate the structural microporosity (MP) and marginal gap (MG) of different flowable composite resins placed with different instruments using micro-computed tomography (μCT). Materials and Methods: Standard Class II MOD cavities were prepared on 108 lower third molar teeth. Three different flowable composite resins; Filtek Bulk-fill, SDR Bulk-fill and I-Flow conventional flowable composite resin were applied to the cavities using a sharp explorer, a microbrush or an injector. After they were covered with a paste-like nanohybrid composite resin, μCT images were examined in terms of MP and MG. Statistical analysis of the data was performed using two-way ANOVA and Tukey's post hoc tests. Results: MP was observed less in explorer group than microbrush and injector groups (p < 0.05). There was no significant difference between microbrush and injector groups (p > 0.05). i-FLOW flowable composite resin showed the highest MP rate compared to the other two groups (p < 0.05). There was no significant difference between SDR and Filtek Bulk-fill in MP (p > 0.05). In terms of MG, i-FLOW presented higher MG values than other two materials (p < 0.05), while the instruments showed similar results (p > 0.05). Conclusions: Additional occluso-gingivally vibration of flowable materials with an explorer may be useful in the placement. Bulk-fill composite resins are better than conventional flowable composite resin in terms of MP and MG.